APPLICATION OF BACILLUS MYCODIES-DERIVED EXOPOLYSACCHARIDES AS A NATURAL PRESERVATIVE COATING TO ENHANCE SHELF LIFE FOR VEGETABLES - S. Dhivya; M. Mekala; R. Ragunathan (The Bioscan, 2025)
The growing demand for safe and eco-friendly alternatives to chemical preservatives has intensified research into biopolymers such as exopolysaccharides (EPS) derived from microbial sources. This study explores the application of Bacillus mycodies-derived EPS as a natural preservative coating for vegetables, assessing its effectiveness in enhancing shelf life and maintaining quality. EPS was isolated and characterized through standard biochemical and structural analyses, confirming its purity and functional properties. Fresh vegetables, including tomatoes, cucumbers, and carrots, were coated with EPS-based solutions and stored under controlled conditions. Comparative analysis was conducted against uncoated samples and samples treated EPS coating. Key parameters such as moisture retention, weight loss, microbial growth, texture, and visual appearance were monitored over a 21-day storage period. The EPS-coated vegetables exhibited significantly reduced microbial spoilage, better moisture retention, and delayed senescence compared to controls. Furthermore, the EPS coating was found to be non-toxic and biodegradable, aligning with sustainability goals. Statistical analyses validated the significant differences (p < 0.05) between EPS-coated and uncoated groups in terms of shelf-life extension and quality preservation. This study highlights the promising potential of Bacillus mycodies EPS as an effective, natural, and eco-friendly alternative to synthetic preservatives in post-harvest technology. KEYWORDS: Bacillus mycodies, Exopolysaccharides, Natural preservative, Vegetable coating, Shelf-life extension.